Redescription of Garra elegans (Günther, 1868), a poorly known species from the Tigris River drainage (Teleostei: Cyprinidae) - Freyhof, Jörg (Zootaxa, 2016)
Tylognathus elegans, from the lower Tigris River drainage in Iraq, was previously placed in Pseudogarra and Hemigrammocapoeta. Studies based on mitochondrial (COI) and nuclear molecular markers (Rhodopsin) place T. elegans in Garra. As the species is poorly known, it is redescribed here.